Bias with respect to socioeconomic status: A closer look at zip code matching in a pneumococcal vaccine effectiveness study. (December 2016) - Link-Gelles, Ruth; Westreich, Daniel; Aiello, Allison E.; Shang, Nong; Weber, David J.; Holtzman, Corinne; Scherzinger, Karen; Reingold, Arthur; Schaffner, William; Harrison, Lee H.; Rosen, Jennifer B.; Petit, Susan; et al.
Abstract: In 2010, 13-valent pneumococcal conjugate vaccine (PCV13) was introduced in the US for prevention of invasive pneumococcal disease in children. Individual-level socioeconomic status (SES) is a potential confounder of the estimated effectiveness of PCV13 and is often controlled for in observational studies using zip code as a proxy. We assessed the utility of zip code matching for control of SES in a post-licensure evaluation of the effectiveness of PCV13 (calculated as [1-matched odds ratio]*100). We used a directed acyclic graph to identify subsets of confounders and collected SES variables from birth certificates, geocoding, a parent interview, and follow-up with medical providers. Cases tended to be more affluent than eligible controls (for example, 48.3% of cases had private insurance vs. 44.6% of eligible controls), but less affluent than enrolled controls (52.9% of whom had private insurance). Control of confounding subsets, however, did not result in a meaningful change in estimated vaccine effectiveness (original estimate: 85.1%, 95% CI 74.8–91.9%; adjusted estimate: 82.5%, 95% CI 65.6–91.1%). In the context of a post-licensure vaccine effectiveness study, zip code appears to be an adequate, though not perfect, proxy for individual SES. Highlights: Socioeconomic status (SES) may impact enrollment in vaccine effectiveness studies. We assessed zip code matching as a proxy for SES in a pneumococcal vaccine study. After zip code matching, we found differences in SES between cases and controls. Differences did not appear to substantially bias estimated vaccine effectiveness.